Measuring and Comparing Hospital Accessibility for Palm Beach County's Elderly and Nonelderly Populations During a Hurricane. (18th September 2017) - Prasad, Shivangi
Abstract: Objectives: To determine whether, during a hurricane, geographic accessibility to hospitals with emergency care is compromised disproportionately for the elderly than for the nonelderly. Methods: The locations of hospitals with emergency health care and a subset of those hospitals functional during a hurricane were compared with the distribution of the elderly population at the block group level in Palm Beach County, Florida. Geographic Information Systems (GIS) proximity analysis (minimum distance to closest hospital) and cumulative distribution functions were used to measure and compare hospital accessibility during normal and hurricane conditions for the elderly and nonelderly populations. Results: Accessibility to closest functional hospital during a hurricane was compromised disproportionately for the elderly. Conclusion: Geographic accessibility to emergency health care is compromised disproportionately for the elderly in Palm Beach County. Compounding the risk is the likelihood of the elderly experiencing a greater health care need during a hurricane. This poses a community public health crisis and calls for effective and collaborative planning between health professionals and disaster planners to address the health care needs of the elderly. ( Disaster Med Public Health Preparedness . 2018; 12: 296–300)